Next Generation Reservoir Engineering. Issue 1 (1st December 2018) - Regenauer-Lieb, Klaus; Poulet, Thomas; Veveakis, Manolis; Roshan, Hamid; Chen, Xiao
Abstract : We present a fundamental physics based understanding of the chemical, mechanical, thermal and hydrological processes and their interactions that operate over long-time scales to form and characterise the porosity/fracture networks in conventional and unconventional oil and gas reservoirs. We apply that understanding to engineer that structure for the purpose of energy extraction and resource discovery. The interdisciplinary approach links geoscience, engineering and computational science disciplines with the result of providing a step change in exploration and exploitation technologies with significant reduction in onshore gas development costs without compromising OHSE or environmental protection and assurance. In this presentation, we will show the first results that allow incorporation of important processes in Unconventional Plays. Surprisingly, diagenetic processes such as the smectite-illite transition are found to create natural fractures under tectonic load that form the permeable reservoirs in Shale Gas/Oil Reservoirs. Results indicate that the fractures triggered by natural fluid release reaction on geological time scales are supported by a critical fluid pressure that must not be crossed to avoid sudden loss of the reservoir. Upon crossing this threshold reservoir damage can be substantial. No amount of proppant or other engineering interaction can rescue the reservoir on a human time-scale. Our novel framework allows to link the long-time scale geological processes with the design of an injection-extraction protocol to maintain critical fluid pressure. We are also able to incorporate micro-structural changes and fluid-solid interaction at grain scale. The latter has only been benchmarked for conventional carbonate plays, but the Multiscale results are encouraging for the entire spectrum of conventional and unconventional traps/source rocks. Our theoretical framework and the forward simulator is specifically designed to interface with geophysical inversion techniques for multi-scale geophysical data. Completing this data-assimilation step in the future will define Next Generation Reservoir Engineering.